Alternative products in the management of green mold in postharvest oranges (Research, Society and Development, 2020)
Green mold, caused by the fungus Penicillium digitatum, is the primary issue in the post-harvest phase of oranges that causes significant losses. Consequently, the objective of this work was to evaluate the effects of alternative products in the management of green mold in postharvest oranges. Four in vitro experiments were conducted. Three assessed the effects of different concentrations of each alternative product (potassium phosphite, Ascophyllum nodosum extract, and organomineral fertilizer) on the production of fresh mycelial weight of P. digitatum; and a fourth evaluated the effects of alternative products compared to that of the conventional product (benzimidazole fungicide). Subsequently, ‘Valencia’ oranges were subjected to the treatments, which consisted of distilled water (inoculated and non-inoculated control), potassium phosphite, A. nodosum extract, organomineral fertilizer, and benzimidazole fungicide. The fruits were inoculated with P. digitatum and evaluated daily for the incidence and severity of green mold over seven days. Furthermore, the effects of the treatments on the physicochemical quality of fruits were evaluated for the following attributes: skin and pulp color, firmness of the pulp, pH, titratable acidity (TA), soluble solids (SS), and the SS/TA ratio. Potassium phosphite and A. nodosum extract inhibited the in vitro development of P. digitatum. The alternative products reduced the incidence and severity of green mold on oranges without compromising the physicochemical quality of the fruit. Therefore, the evaluated products can be used in the postharvest treatment of oranges and are considered promising alternatives for the management of green mold.